Balanced anesthesia in pigeons (Columba livia): a protocol that ensures stable vital parameters and feasibility during long surgeries in cognitive neuroscience - Serir, A.; Tuff, J. M.; Rook, N.; Fongaro, E.; Schreiber, T.; Peus, E.; Güntürkün, O.; Manahan-Vaughan, D.; Rose, J.; Pusch, R. (Frontiers in Physiology, 2024)
In neuroscience, numerous experimental procedures in animal models require surgical interventions, such as the implantation of recording electrodes or cannulas before main experiments. These surgeries can take several hours and should rely on principles that are common in the field of research and medicine. Considering the characteristics of the avian respiratory physiology, the development of a safe and replicable protocol for birds is necessary to minimize side effects of anesthetic agents, circumvent technical limitations due to the insufficient availability of patient monitoring, and to maintain stable intraoperative anesthesia. Through the consistent and responsible implementation of the three R principle of animal welfare in science ('Replace, Reduce, Refine'), we aimed to optimize experimental methods to minimize the burden on pigeons (Columba livia) during surgical procedures.Here, surgeries were conducted under balanced anesthesia and perioperative monitoring of heart rate, oxygen saturation, body temperature, and the reflex state. The protocol we developed is based on the combination of injectable and inhalative anesthetic drugs (ketamine, xylazine, and isoflurane, supported by the application of an opiate for analgesia (e.g. butorphanol, buprenorphine). The combination of ketamine and xylazine with a pain killer is established in veterinary medicine across a vast variety of species. Practicability was verified by survival of the animals, fast and smooth recovery quantified by clinical examination, sufficiency, and stability of anesthesia. Independent of painful stimuli like incision or drilling, or duration of surgery, vital parameters were within known physiological ranges for pigeons. Our approach provides a safe and conservative protocol for surgeries of extended duration for scientific applications as well as for veterinary medicine in pigeons which can be adapted to other bird species.